The efficacy and safety of a nicotine conjugate vaccine (NicVAX(®)) or placebo co-administered with varenicline (Champix(®)) for smoking cessation: study protocol of a phase IIb, double blind, randomized, placebo controlled trial - Hoogsteder, Philippe HJ (BioMed Central, 2012)
BACKGROUND: A potential new treatment in smoking cessation and relapse prevention is nicotine vaccination which is based on active immunization against the nicotine molecule. This immunization will elicit the immune system to produce nicotine-specific antibodies that sequester nicotine in the blood stream, after inhaling tobacco products. The resulting antibody-antigen is too large to cross the blood–brain barrier and is therefore postulated to attenuate the rewarding effect of nicotine by preventing the latter from reaching its receptors in the brain and causing the release of dopamine. The aim of this paper is to describe the design of a phase IIb, multi-center, double blind, randomized, placebo controlled trial to assess the efficacy of the nicotine vaccine NicVAX(®) co-administered with varenicline (Champix(®)) and intensive counseling as an aid in smoking cessation and relapse prevention. METHODS/DESIGN: Two centers will include a total of 600 smokers who are motivated to quit smoking. At week −2 these smokers will be randomized, in a 1:1 ratio, to either 6 injections of NicVAX(®) or placebo, both co-administered with 12-weeks of varenicline treatment, starting at week 0. The target quit day will be set after 7 days of varenicline treatment at week 1. Smokers will be followed up for 54 weeks. The primary outcome is defined as biochemically validated prolonged smoking abstinence from week 9 to 52. Secondary outcomes include safety, immunogenicity, smoking abstinence from week 37 to 52, abstinence from week 9 to 24, abstinence in the subset of subjects with the highest antibody response, and lapse/relapse rate. DISCUSSION: This is the first study to assess the efficacy of a nicotine conjugate vaccine in combination with an evidence-based smoking cessation pharmacotherapy (varenicline) to quit smoking. Although NicVAX(®) is primarily designed as an aid to smoking cessation, our study is designed to explore its potential to maintain abstinence and prevent relapse. The results of this trial will give a unique insight in the potential of nicotine vaccination for relapse prevention. TRIAL REGISTRATION: ClinicalTrials.gov: (NCT00995033)